Effectiveness of Video-assisted Teaching on Anxiety Related to Labor Process and Preparation for Labor Among the Primigravida Mothers Attending Antenatal OPD at GMCH-32 Chandigarh - Bhola Himani; Kaur Ramandeep; Bhawna; Prakash Chetan; Sachdeva Divya; Khan Firoz; Garima; Randhawa Gulbagh (International Journal of Midwifery Nursing And Practices, 2024)
Aims and background: A randomized control trial to assess the effectiveness of video-assisted teaching on anxiety related to labor process and preparation for labor among primigravida mothers attending antenatal OPD of GMCH-32, Chandigarh, was carried out in full compliance with ethical standards laid down by the Research and Ethical Committee of GMCH-32, Chandigarh. Method: A systematic random sampling technique was used to select 80 subjects, 40 each in control and experimental group, who were attending the antenatal OPD of GMCH-32, Chandigarh. Results: The study revealed that primigravida mothers of experimental group have lesser anxiety than primigravida mothers of control group. Conclusion: It is concluded that video-assisted teaching is an effective intervention for the reduction of anxiety among primigravida mother.
Keywords: Anxiety; Pregnancy; Video assisted teaching; antenatal period; labor process; primigravida mother; randomization